FEATURES OF POSTNATAL DEVELOPMENT OF THE LIVER OF THE OFFSPRING UNDER CHRONIC EXPOSURE TO AIR POLLUTANTS ON THE MOTHER'S BODY (Modern American Journal of Medical and Health Sciences, 2026)
The study presents the results of an experimental investigation of the effects of chronic exposure to atmospheric air pollutants on the postnatal liver development of offspring. Morphological, immunohistochemical, and morphometric changes were identified, characterized by decreased hepatocyte proliferation, increased apoptosis, disruption of sinusoidal architecture, and early activation of fibrogenesis. The obtained data indicate the formation of prerequisites for metabolic disorders in later stages of life.